ANALYSIS OF FINANCIAL PERFORMANCE ASSESSMENT USING THE CAMEL METHOD AT THE MAIN BRANCH OF PT BANK SULSELBAR IN MAKASSAR CITY - Sriandara Salman; Tenri Sayu Puspitaningsih Dipoatmodjo, Andi Mustika Amin, Muh. Ichwan Musa, Anwar (ADISAM Publisher, 2022)
This study aims to analyze financial performance in terms of the soundness of the bank at the PT. Bank Sulselbar Makassar Main Branch using the CAMEL method. The type of research used is descriptive quantitative. The population in this study is the financial statements of PT Bank Sulselbar Makassar Main Branch from 2016-2021. While the sample in this study is the Financial Statements in the form of a Balance Sheet and Income Statement of PT. Bank Sulselbar Makassar Main Branch 2016 to 2021. Data analysis technique using the CAMEL method (Capital, Asset Quality, Management, Earning, Liquidity). The results showed that the calculation of the CAMEL ratio in 2016 was in the Healthy category and for 4 consecutive years in 2017 to 2020 it was in the Fairly Healthy category and in 2021 there was an increase in the Healthy category. Thus it can be concluded that the financial performance of PT. Bank Sulselbar Makassar Main Branch in 2016 – 2021 using the CAMEL method is in the Pretty Healthy predicate for 4 consecutive years in the Fairly Healthy category.